Characteristics of Pap Smear Cytology Using LBC in Gynecological Patients at Siloam West Jakarta from 2023 to 2025 - Talitha Athayarahma; Welly Hartono Ruslim (Greenation Publisher & Yayasan Global Research National, 2026)
Cervical cancer remains a major public health problem worldwide, particularly in developing countries, including Indonesia. Early detection through screening plays a crucial role in reducing morbidity and mortality. This study aimed to describe the cytological findings of Pap smears using the Liquid-Based Cytology (LBC) method based on the Bethesda system, as well as to analyze patient characteristics and HPV infection status among gynecological patients at Siloam West Jakarta Hospital from 2023 to 2025. This research employed a descriptive retrospective design using secondary data from the medical records of 823 patients. The variables analyzed included age, hormonal status, parity, clinical symptoms, cytology results, and HPV infection status. The results showed that most patients were aged 30–49 years and in the reproductive hormonal phase. The majority of cytological findings were categorized as Negative for Intraepithelial Lesion or Malignancy (NILM), with smaller proportion showing epithelial cell abnormalities, predominantly Atypical Squamous Cells of Undetermined Significance (ASC-US). HPV infection was detected in a minority of patients. The findings indicate that LBC is effective in identifying cervical cytology profiles and supporting early detection programs. Strengthening screening programs, particularly in high-risk populations, is essential to improve early diagnosis and prevention of cervical cancer.